Optimalisasi Pengetahuan Remaja Tentang Anemia dan Pemanfaatan Smoothies ABC (Anemia Booster Cocktail) Sebagai Minuman Alternatif di SMPN 1 Cimalaka: Pengabdian - Risna Mutiara; Fasya Nabila; Asfi Hanifah Lisdiana; Nirina Hanifah Safanissa; Muhammad Rendy Rivaldy; Roihan Khoirurozak; Nena Dwi Cahya; Fakhri Habibi; Fina Faradilla; Miftah Fajar Raihan Firmansyah; Muhtadin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Adolescents need balanced nutritional intake that is useful for optimizing growth and development, adolescents are classified as a vulnerable group for malnutrition, one of which is anemia. This community service was carried out at SMPN 1 CIMALAKA in 2025, with data based on SKI in 2023, namely 15.5% of anemia sufferers in Indonesia. One of the problems of anemia in adolescents is the lack of understanding in prevention efforts in adolescents. The method used is the lecture method, namely by explaining in a structured manner, and evaluation is carried out after the delivery of the material by asking random participants regarding the understanding of the counseling material. The delivery of alternative drink innovations to increase iron intake in the body is ABC smoothies with papaya and banana as the basic ingredients, with honey as a sweetener. Smoothies as one of the non-pharmacological approaches carried out as a preventive effort in overcoming anemia in adolescents. The increase in understanding regarding anemia in SMPN 1 CIMALAKA students was assessed subjectively by assessing a sampling of 3 participants to re-explain the counseling material and in accordance with what was conveyed. The innovation of alternative ABC smoothie drinks can be a non-pharmacological measure to increase iron intake into the body.